Distribution of Dental Caries among Primary School Children in Al-Mukalla Area, Yemen - AM. Al-Haddad; AS. Bin Ghouth; HS. Hassan (Tehran University of Medical Sciences, 2006)
Statement of problem: Dental caries are considered as one of the most common health problems and have been shown to be more prevalent in children. Purpose: The aim of this cross-sectional study was to determine the distribution of dental caries among 400 twelve-year-old schoolchildren, in the Al-Mukalla area in Yemen. Materials and Methods: Multistage stratified sampling was used to obtain a sample size of 400 children, consisting of 200 males and 200 females with mixed dentitions. All subjects were selected from two private schools and five public schools. Clinical examinations were performed under standardized conditions by a trained examiner. Results: Dental caries was found in 198 (49.5%) of the 400 schoolchildren including 51.5% males and 48.5% females. The prevalence of caries was higher (p